The relationship between liver function tests and sociodemographic- clinical characteristics of alcohol dependent patients - Mırsal, Hasan; Pektaş, Özkan; Kalyoncu, O. Ayhan; Beyazyürek, Mansur (Journal of Dependence, 2002)
Objective: There are some biochemical factors that are commonly used as screening tests for alcohol use disorders. The well-known liver function tests including SGOT-(AST), SGPT- (ALT), GGT were widely studied in clinical use. In this study, the relationship between liver function tests and sociodemographic-clinical characteristics of alcohol dependent patients were evaluated.Method: In this study, 312 patients were diagnosed as alcohol dependent according to DSM-IV criteria. All patients were treated as inpatient during the year 1998. The sociodemographic and clinical characteristics of patients were examined by a detailed data sheet. Blood samples were collected in the morning and concealed at optimal conditions. Measures were done at the same calibration value in designated interval all at once. The relationship between sociodemographic-clinical characteristics and laboratory results were evaluated by SPSS statistics programme.Results: Twenty-seven female (8,7 %) and 285 male (91,3 %) patients were included in this study. The mean age of the sample was 41,0 years (sd = 9,0) and the mean age of initiation for alcohol use was 19,5 years (sd = 5,3). The results of statistical evaluation were determined as follows: There are significant differences among GGT levels according to gender, starting age to drink and withdrawal symptoms.Conclusion: The duration and level of alcohol consumption determine the liver function test abnormalities. The role and importance of biological markers in alcohol dependence should be studied by detailed prospective-controlled studies.
Keywords: alcohol dependence; sociodemographic characteristics; liver function tests